2016
DOI: 10.21614/chirurgia.111.5.400
|View full text |Cite
|
Sign up to set email alerts
|

Digestive Decompression to Prevent Digestive Fistulas After Gastric Neoplasm Resection

Abstract: Rezumat Decompresia digestivã în prevenåia fistulelor digestive dupã rezecåia gastricã pentru neoplasmIntroducere: Riscul de fistulã digestivã la pacienåii operaåi pentru neoplasm gastric este crescut datoritã dezechilibrelor biologice generate de evoluåia cancerului, de stadiile avansate la prezentare aei de amploarea intervenåiei. În aceste condiåii utilizarea unor metode tehnice care sã protejeze suturile digestive la aceaeti pacienåi este utilã. Scop: Analiza eficienåei mijloacelor tehnice de protejare a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…DSF pathogenesis remains unknown [2]. Main risk factors may be devascularization of duodenal stump or its inadequate surgical closure, inflammation of duodenal wall, local hematoma, neoplastic involvement of resection line, incorrect abdominal drain placement, and postoperative distension of the duodenum due to distal obstruction [2, 23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DSF pathogenesis remains unknown [2]. Main risk factors may be devascularization of duodenal stump or its inadequate surgical closure, inflammation of duodenal wall, local hematoma, neoplastic involvement of resection line, incorrect abdominal drain placement, and postoperative distension of the duodenum due to distal obstruction [2, 23].…”
Section: Discussionmentioning
confidence: 99%
“…For subtotal gastrectomy, Marincas et al recently suggested the use of an intraoperatively introduced duodenal decompression probe, with the aim of reducing DSF risk [23]. However, the results were unsatisfactory [23].…”
Section: Discussionmentioning
confidence: 99%
“…The surgical stress determines, apart from the metabolic and endocrine reactions, also ample immune reactions. The excess of lipid and protein catabolism, the diminution of the anabolic effect of insulin and the insulin resistance, all on the one side and the inflammatory reaction, with the increase in the levels of Il-6, I-l1, TNF, and C reactive protein, on the other side, can require a lot from the resources of the cancer patient (2). Both the surgical intervention and the anaesthesia can alter the mechanisms of defence and depress the essential natural killer cells and also decrease their activity in the destruction of cancer cells (12).…”
Section: Discussionmentioning
confidence: 99%
“…All these, next to the correct execution of the manual suture, or of the mechanical one, contribute to the avoidance of the appearance of fistulas. The implementation of the measures of protection of the anastomoses (such as the installation of the duodenal decompression tube in patients with palliative limited gastric resections and with gastrojejunal anastomosis, of the gastric aspiration tube when the gastric stump is kept, and the use of the oesophageal tube in total gastrectomy), have the role to diminish the pressure in the area of the anastomoses in the immediate postoperative period (2).…”
Section: Introductionmentioning
confidence: 99%
“…However, edema of the stomach and malnutrition lower the function of immune system, which increases the risk of perioperative complications ( 2 ). To avoid complications such as infection, anastomotic leakage, and preoperative decompression of the stomach, nutrition therapy is necessary in these patients ( 5 ).…”
Section: Introductionmentioning
confidence: 99%